Exploring the Role of Instagram Video Blogging in Enhancing Engagement in a Foreign Language Classroom - Puspitasari, Dani; Yoedo, Yuli Christiana; Weng, Cathy (JOLLT Journal of Languages and Language Teaching, 2025)
Taiwanâ€™s ministry of education urges all education levels to open foreign language programs, including Indonesian language, in their institution. Yet, this encouragement is not followed by adequate propaganda. Hence, innovative engagement strategies are needed to make Indonesian language elective courses popular in Taiwan.Â Thus, an Indonesian native speaker teacher of a northern Taiwan public university integrated Instagram in her elective course to enhance engagement. She assigned her students to make a video blog with the theme â€œself-introductionâ€ and upload the video to their social media. This media is used due to its significant impact on everyday life. This study probes social media’s impact on video blogging projects and how learners with different mastery goal levels identified their engagement and satisfaction after finishing the project. Fourteen students participated in this study, and the data were gathered through in-depth interviews and self-reported online journals. The interview and online guided journal generated students’ self-monitoring, behavioral engagement, and satisfaction. Screenshots from the student’s post on Instagram and social media chat also served as evidence to support the findings. The result shows the significant influence of social media on learners’ effort and creativity in doing the assignment; it also influences the satisfaction regarding the participants’ mastery approach. Students poured their endeavors exceeding the teacherâ€™s expectation. To ensure the quality of the video content, they did a lot of self-practices and consultations with their teacher. The result leads to the pedagogical implications of integrating video blogging and social media within authentic learning environments for enhanced student engagement.